Myositis in mixed connective tissue disease: a unique syndrome characterized by immunohistopathologic elements of both polymyositis and dermatomyositis Miosite na doença mista do tecido conectivo: achados imunopatológicos de polimiosite e dermatomiosite - Maria Angela A.G. Vianna; Claudia T.L. Borges; Eduardo F. Borba; Maria Teresa C. Caleiro; Eloisa Bonfá; Suely K.N. Marie (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To characterize the inflammatory cells, the expression pattern of adhesion molecules (ICAM-1 and VCAM-1), membrane attack complex (C5b-9), and major histocompatibility complex (MHC) antigens in muscle biopsy of mixed connective tissue disease (MCTD). METHOD: We studied 14 patients with MCTD, and compared to 8 polimyositis (PM) patients, 5 dermatomyositis (DM) and 4 dystrophies. Inflammatory cells were examined for CD4+, CD8+, memory and naïve T cells, natural killer cells, and macrophages. Expression of MHC-I and -II, ICAM-1, VCAM-1 and C5b -9 were characterized on muscle fibers and vessels. RESULTS: Morphological analysis displayed a pattern of PM. Immunohistochemical study revealed a decreased number of capillaries, predominance of CD4+ and B cells in perivascular regions and predominance of CD8+ and CD45RO+ in endomysial regions. The expression of MHC-I on vessels and on degenerated muscle fibers, MHC-II expression on vessels and perifascicular muscle fibers, and the expression of ICAM-1 / VCAM-1 on endothelial cells indicated both vascular and cellular-immune mediated processes causing the muscular lesion. CONCLUSION:Our findings revealed a mixed mechanism in MCTD, both vascular involvement as DM, and cell-mediated like PM. OBJETIVO: Caracterizar as células do infiltrado inflamatório, o padrão de expressão das moléculas de adesão (ICAM-1 e VCAM-1), complexo de ataque à membrana (C5b-9) e antígenos de histocompatibilidade maior (MHC) em biópsias musculares de patientes com doença mista do tecido conectivo (DMTC). MÉTODO: Foram estudados14 pacientes com DMTC e comparadas com 8 pacientes com polimiosite (PM), 5 com dermatomiosite (DM) e 4 com distrofias. As células inflamatórias foram caracterizadas como CD4+, CD8+, células T de memória (CD45RO+) e virgens, células "natural killer" e macrófagos. As expressões de MHC-I e -II, ICAM-1, VCAM-1 e C5b-9 foram caracterizadas em fibras musculares e vasos. RESULTADOS:A análise morfológica demonstrou um padrão tipo PM. O estudo imuno-histoquímico revelou diminuição do número de capilares, predomínio de células CD4+ e B nas regiões perivasculares e predomínio de CD8+ e CD45RO+ nas regiões endomisiais. A expressão de MHC-I nos vasos e nas fibras degeneradas, MHC-II nos vasos e fibras perifasciculares e expressão de ICAM-1 / VCAM-1 no endotélio indicaram uma associação de processos vascular e imune-celular mediando a lesão muscular. CONCLUSÃO: Os achados revelaram duplo mecanismo na DMTC, imune-celular como na PM e vascular como na DM.